1992
DOI: 10.4315/0362-028x-55.4.246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cleaners and Sanitizers on Listeria monocytogenes Attached to Product Contact Surfaces

Abstract: A variety of chemical cleaning and sanitizing compounds were evaluated for their ability to remove and/or inactivate surface adherent Listeria monocytogenes. Adherent cells were obtained by incubating 1-cm2 chips of stainless steel or plastic conveyor belts with a multistrain cocktail of L. monocytogenes for 24 h at 25°C. Resistance of adherent cells to sanitizers was dependent upon the surface studied, being greatest on polyester/polyurethane followed by polyester and stainless steel. Biofilm removal with cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(109 citation statements)
references
References 0 publications
10
95
1
3
Order By: Relevance
“…There have been reports of results similar to our experiment (13). In this research, the hygienic conditions of 86 different surfaces of a line of fluid milk in 4 dairy plants were evaluated by the ATP bioluminescence technique and mesophilic aerobic counts.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…There have been reports of results similar to our experiment (13). In this research, the hygienic conditions of 86 different surfaces of a line of fluid milk in 4 dairy plants were evaluated by the ATP bioluminescence technique and mesophilic aerobic counts.…”
Section: Resultssupporting
confidence: 70%
“…In our experiment, the influence of chemical agent residues, basically sodium hydroxide applied to remove organic substances, such as proteins and fats from surfaces was not evaluated, but some researches have demonstrated that the RLU measurement can be affected by chemical cleaning agents and commercial sanitizers (9,10,13). An ATP extractant effect is attributed to detergents and sanitizers solutions used in cleaning and sanitizing procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Our results contrast with those of other authors (KRYSINSKI; BROWN; MARCHISELLO, 1992;RONNER;WONG, 1993;ABRISHAMI et al, 1994;BOURION;CERF, 1996;LINDSAY;VON HOLY, 1999;BREMER;MONK;BUTTLER, 2002), who reported that resistance of bacteria to sanitizers was influenced by the type of surface. These discrepancies could be explained, at least in part, by the fact that they challenged different sanitizers, bacterial species, or attachment surfaces.…”
Section: Effect Of Heatcontrasting
confidence: 99%
“…To this respect, there are several reports on the in vitro capacity of these bacteria to adhere to stainless steel laminae and/or synthetic polymers [14][15][16][17][18].…”
Section: Open Access Research Articlementioning
confidence: 99%
“…To this respect, there are several reports on the in vitro capacity of these bacteria to adhere to stainless steel laminae and/or synthetic polymers [14][15][16][17][18].Bacterial adhesion to a surface is a two-phases process: in the first phase, planktonic bacteria are moved to a surface by the effect of physical forces such as Brownian motion, van der Waals attraction forces, gravitational forces, the effect of surface electrostatic charge and hydrophobic interactions; in the second phase of adhesion, molecular irreversible reactions between bacterial surface structures and substratum surfaces become predominant [19,20]. Adhesion is an essential stage for the formation and subsequent growth of biofilms [19,21,22].…”
mentioning
confidence: 99%